2021
DOI: 10.1021/acs.langmuir.1c01681
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Etching of Silicon Assisted by Graphene Oxide in an HF–HNO3 Solution and Its Catalytic Mechanism

Abstract: Chemical etching of silicon assisted by various types of carbon materials is drawing much attention for the fabrication of silicon micro/nanostructures. We developed a method of chemical etching of silicon that utilizes graphene oxide (GO) sheets to promote the etching reaction in a hydrofluoric acid–nitric acid (HF–HNO3) etchant. By using an optimized composition of the HF–HNO3 etchant, the etching rate under the GO sheets was 100 times faster than that of our HF–H2O2 system used in a previous report. Kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…After oxygen moieties on GO sheets were removed at the beginning of the etching process, the chemical condition of GO sheets was not changed. This behavior was consistent with our previous findings 22,23 and indicated that a strong oxidant, H 2 O 2 or HNO 3 , in the vapor etchant did not oxidize GO sheets but was consumed in the etching reaction.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…After oxygen moieties on GO sheets were removed at the beginning of the etching process, the chemical condition of GO sheets was not changed. This behavior was consistent with our previous findings 22,23 and indicated that a strong oxidant, H 2 O 2 or HNO 3 , in the vapor etchant did not oxidize GO sheets but was consumed in the etching reaction.…”
Section: Resultssupporting
confidence: 93%
“…48 We also discussed the relationship between GO structures and the etching rate and proved that defects on GO contributed to its catalytic property in liquid-phase etching. 23 The surface chemical condition of silicon after vapor-phase etching depended on the composition of the etching solution prepared; however, GO-covered areas were etched faster than noncovered areas under all conditions in our experiments. With a high oxidant concentration etchant, a silicon oxide layer formed on the silicon surface.…”
Section: + + +mentioning
confidence: 62%
See 3 more Smart Citations